Tafsir of Ijarah and Ujrah Versesin the Application of Muamalah - Islamiah, Ifa Nurul; Sunandar, Heri (International Journal Labs, 2023)
Muamalah is a part of Islamic teachings that regulate relations between individuals. One activity in muamalah is ijarah, which is renting goods where the lessor receives rent or compensation. Although ijarah has rules that must be followed, there are still many ijarah practitioners who do not understand the legal basis and rules that apply. This study discusses Quranic verses on ijarah, requirements of ijarah, payment of ujrah, cancellation of ijarah contract, return of rented goods, types of ijarah, and application of ijarah in everyday life. A qualitative method with a literature study type was used to collect data from written sources such as books, journals, and other sources related to ijarah. The results of this study indicate that ijarah refers to an agreement to use goods or services by paying rent, but does not include the transfer of ownership of the goods. Ijarah is often used in everyday life to rent labour and goods. There are two types of ijarah in financial transactions, namely ijarah and ijarah muntahiya bittamlik. The ijarah contract itself is divided into two types, namely ijarah al'ain and ijarah al-dzimmah. However, ijarah muntahiya bittamlik is declared haram if there are two contracts in one transaction. The solution is to separate the lease contract and the sale contract by first conducting the lease contract and then conducting the sale contract after the lease contract is completed. The law of ijarah almuntahiya bitamlik is haram, if there are two contracts in one transaction, and the solution to permissible ijarah muntahiya bittamlik is by separating contracts, namely by first conducting the lease contract and if the lease contract is complete then using a new contract with the sale contract.